THE EDITOR'S RECOMMENDATION OF THIS ISSUE'S ARTICLE TO READERS - Burak Buldur (Cumhuriyet University, 2020)
I am pleased to inform you that I have chosen this article by Geduk et al.1 as Editor's Choice for this issue of 2020. Planning dental and gingival analyzes after the facial, dentolabial and phonetic parameters is critical to achieve successful esthetic results This article revealed that there is no consensus between esthetically objective findings and subjective views. Happy readings in the third issue of 2020! I am pleased to inform you that I have chosen this article by Geduk et al.1 as Editor's Choice for this issue of 2020. Planning dental and gingival analyzes after the facial, dentolabial and phonetic parameters is critical to achieve successful esthetic results This article revealed that there is no consensus between esthetically objective findings and subjective views. Happy readings in the third issue of 2020!